Analysing Stokvels Development Through the Lens of Layered Conceptual Framework - Bophela, Mduduzi Justice Kennedy (Technium Social Sciences Journal, 2022)
Despite the popularity of stokvels, there is dearth in studies to develop integrated models of stokvels. This study intends to provide a conceptual framework for developing an integrated framework by layering each component of the Maslow’s hierarchy of need and Hayes & Wheelwright business models. Simple random method was adopted on 395 stokvelgroup’s members who were administered with a questionnaire and the purposive sampling method on 6 MC members of eThekwini Municipality that participated in the interviews. The qualitative data was analysed using N-VIVO (version 11.0). The quantitative data was analysed using inferential and descriptive statistics. A new model layering Maslow’s theory with the Hayes & Wheelwright four-stage model was developed using a theory triangulation technique to validate the theories with the findings of the study.